LITERATURE REVIEW OPTIMALISASI PENGELOLAAN SUMBER DAYA DAN MITIGASI RISIKO MELALUI BUSINESS INTELLIGENCE: PENDEKATAN STRATEGIS - Siregar, Sarah Veronica; Tjahjono, Budi; Nurjannah, Nurjannah; Basyarewan, Humairoh (Politeknik Bisnis Indonesia, 2024)
Rapid business developments require organizations to be smarter in managing resources and reducing risks in order to remain competitive. This study aims to explore the strategic role of Business Intelligence (BI) in helping organizations achieve these goals. Through a comprehensive literature review, this study analyzes various BI tools and techniques used to optimize resources, such as labor, finance, and materials, and identify risks early. The results show that BI can improve operational efficiency by providing data-based insights, supporting better decision-making, and proactively mitigating risks. BI can help organizations monitor financial data in real time to prevent the risk of loss, or predict energy needs to prevent waste. In addition, a strategic approach to implementing BI, such as choosing the right tools and involving leaders, is a key factor in success. This study concludes that BI has great potential to help organizations become more resilient and efficient, while providing practical guidance for companies that want to use BI to manage resources and risks effectively.